2014
DOI: 10.1371/journal.pone.0104931
|View full text |Cite
|
Sign up to set email alerts
|

Role of Far Infra-Red Therapy in Dialysis Arterio-Venous Fistula Maturation and Survival: Systematic Review and Meta-Analysis

Abstract: IntroductionA well-functioning arteriovenous fistula (AVF) is the best modality for vascular access in patients with end-stage renal disease (ESRD) requiring haemodialysis (HD). However, AVFs’ main disadvantage is the high rate of maturation failure, with approximately one third (20%–50%) not maturing into useful access. This review examine the use of Far-Infra Red therapy in an attempt to enhance both primary (unassisted) and secondary (assisted) patency rates for AVF in dialysis and pre-dialysis patients.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
(60 reference statements)
1
30
0
Order By: Relevance
“…Chapter 8 covers longterm patency of AV fistulas and AV grafts. We identified seven systematic reviews of RCTs assessing benefits and harms of various medical adjuvant treatments to increase overall patency of AV fistulas and AV grafts [13][14][15][16][17][18][19]. All these reviews were judged to be of moderate to high quality with AMSTAR scores of 8-10/11.…”
Section: Rationale • Backgroundmentioning
confidence: 99%
“…Chapter 8 covers longterm patency of AV fistulas and AV grafts. We identified seven systematic reviews of RCTs assessing benefits and harms of various medical adjuvant treatments to increase overall patency of AV fistulas and AV grafts [13][14][15][16][17][18][19]. All these reviews were judged to be of moderate to high quality with AMSTAR scores of 8-10/11.…”
Section: Rationale • Backgroundmentioning
confidence: 99%
“…The superiority of haemodialysis (HD) access created by means of an Arteriovenous Fistula (AVF) in patients with end stage renal disease (ESRD) has been shown before. Stenosis and thrombosis is less likely to occur in a well-functioning mature AVF when compared to arteriovenous grafts (AVG) and central venous catheters (CVC), resulting in prolonged patency rates for AVFs as has been described previously [ 1 ]. Also, AVFs carry a lower risk for infection [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that a lower haemoglobin level was associated with better functional maturation rates; we hypothesise that this might be explained by the up-regulation of endothelial Nitric Oxide Synthase (eNOS) in the newly formed conduit, leading to increased production of Nitric Oxide (NO) and Haeme Oxygenase-1 (HO-1) as a result of the relative hypoxia status caused by lower haemoglobin levels in the blood. NO is associated with vasodilation and decreased cellular proliferation [38], whereas HO-1 has been shown to inhibit proliferation of vascular smooth muscle cells, platelet aggregation, and vasospasm [3]. However, those are mere speculations and further studies aimed to specifically test the association of those markers and fistula maturation are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A mature and functional arteriovenous fistula (AVF) is considered the best modality for HD access when compared to arteriovenous grafts (AVG) and central venous catheters (CVC) [3][4][5], however it is expected that approximately one third (20%-50%) of AVFs will fail to mature into useful access [6][7][8]. Although the chances for an AVF to fail are high, they should still be considered first in all patients planned to start HD sessions, and for the ones who have already started HD.…”
Section: Introductionmentioning
confidence: 99%